MICROWAVE-ASSISTED SYNTHESIS AND CHARACTERIZATION OF ZNO NANOPARTICLES - Geetha N B,; Sindhuja A,; Boopathy. G,; Ramya. R, (The Bioscan, 2025)
A spinel ZnO nanocatalyst was successfully synthesized via a direct microwave heating method. X-ray diffraction (XRD) analysis confirmed the formation of a single-phase cubic spinel gahnite structure (ZnAl₂O₄) with a calculated lattice parameter of 8.335 Å, indicating high phase purity. The average crystallite size, estimated using the Debye-Scherrer equation, was approximately 26.53 nm. Fourier-transform infrared (FT-IR) spectroscopy revealed characteristic metal–oxygen stretching vibrations, corroborating the spinel structure. High-resolution scanning electron microscopy (HR-SEM) images displayed well-defined, nano-sized grains with uniform morphology, suggesting effective control over particle formation. These findings demonstrate that microwave-assisted synthesis is a viable and efficient approach for producing high-purity spinel ZnO nanocatalysts with desirable structural and morphological properties.